Short, large-amplitude speed enhancements in the near-Sunfast solar wind. Issue 2 (26th April 2018) - Horbury, T S; Matteini, L; Stansby, D
ABSTRACT: We report the presence of intermittent, short discrete enhancements in plasma speed in the near-Sun high-speed solar wind. Lasting tens of seconds to minutes in spacecraft measurements at 0.3 au, speeds inside these enhancements can reach 1000 km s −1, corresponding to a kinetic energy up to twice that of the bulk high-speed solar wind. These events, which occur around 5 per cent of the time, are Alfvénic in nature with large magnetic field deflections and are the same temperature as the surrounding plasma, in contrast to the bulk fast wind which has a well-established positive speed–temperature correlation. The origin of these speed enhancements is unclear but they may be signatures of discrete jets associated with transient events in the chromosphere or corona. Such large short velocity changes represent a measurement and analysis challenge for the upcoming Parker Solar Probe and Solar Orbiter missions.